Empowering Students’ Reading Comprehension through Paired Reading Method at the Tenth Grade of SMA Negeri 14 Maluku Barat Daya - Meyer, Fredi; Kakerissa, Wenda Marlin (Koli Journal : English Language Education, 2025)
This classroom action research study aimed to enhance and empower reading comprehension among tenth-grade students at SMA Negeri 14 Maluku Barat Daya through the systematic application of the paired reading method. The study sought not only to improve students’ technical reading skills but also to foster greater self-efficacy and motivation by engaging them in structured peer learning. Baseline assessments revealed that many students faced challenges when reading individually, highlighting the need for a collaborative instructional approach. In Cycle 1, the intervention was implemented with strategic pairing based on reading proficiency and enhanced teacher facilitation; the results indicated that approximately 64% (16 out of 25) of the students met the predetermined reading comprehension benchmark. Based on these findings, refinements were made for Cycle 2 including improved pairing strategies, increased scaffolding, and more rigorous data management—which culminated in all 25 students (100%) achieving the benchmark. These outcomes demonstrate that iterative application of the paired reading method can significantly elevate reading comprehension outcomes while simultaneously empowering students through collaborative learning. This study contributes to the growing body of evidence supporting classroom action research as an effective means for refining instructional practices, and its findings underscore the potential benefits of peer-assisted reading strategies in secondary education.